Association of oxidative stress and inflammatory markers with chronic stress in patients with newly diagnosed type 2 diabetes. Issue 5 (25th March 2019) - Siddiqui, Azaz; Desai, Nimesh G.; Sharma, Suman B.; Aslam, Mohammad; Sinha, Uday K.; Madhu, Sri V.
Abstract: Aims: Chronic stress is associated with increased risk of type 2 diabetes. Oxidative stress and inflammation are potential mediators of this risk. This study was conducted to investigate the association of oxidative stress and inflammatory markers with chronic stress and newly diagnosed type 2 diabetes. Methods: Oxidative stress/antioxidant status (malondialdehyde [MDA], reduce glutathione [GSH], glutathione reductase [GR], glutathione peroxidase [GPx], catalase [CAT], superoxide dismutase [SOD]), inflammatory markers (highly sensitive C‐reactive protein [hsCRP], adiponectin, leptin), chronic stress levels as assessed by stress scales—presumptive stressful life events scale (PSLES), perceived stress scale (PSS), sense of coherence (SOC) and stress biomarker—salivary cortisol in 125 subjects with newly detected diabetes mellitus (NDDM) were compared with an equal number of age and sex matched subjects with normal glucose tolerance (NGT). Results: NDDM subjects as compared with NGT had significantly increased MDA ( P  < 0.001), hsCRP ( P  < 0.001), and leptin ( P  = 0.014) levels and increased GR ( P  = 0.043) and SOD ( P  < 0.001) activity along with decreased GSH ( P  < 0.001) and adiponectin ( P  < 0.001) levels. They also had significantly higher PSLES‐LT and PSS and lower SOC scores along with elevated levels of 10:00 pm salivary cortisol and post dexamethasone salivary cortisol as compared with NGT. In stepwise logistic regression analysis, variables GSH (OR: 0.805), SOD (OR: 1.004), and adiponectin (OR: 0.771) along with PSLES‐LT (OR: 1.007), PSS (OR: 1.147), SOC (OR: 0.667), salivary cortisol 10:00 pm (OR: 1.382), WC (OR: 1.087), and HOMA‐IR (OR: 2.721) emerged as significant predictors of NDDM. Conclusion: The findings of this study indicate that chronic psychological stress and stress responses are associated significantly with inflammation and oxidative stress, which could act as mediating stress related risk factors for type 2 diabetes.